2015
DOI: 10.1039/c5ra17953j
|View full text |Cite
|
Sign up to set email alerts
|

Powder activated carbon/Fe3O4 hybrid composite as a highly efficient heterogeneous catalyst for Fenton oxidation of tetracycline: degradation mechanism and kinetic

Abstract: In this work, we prepared and used a composite of powder activate carbon/Fe 3 O 4 magnetic nanoparticles (PAC/Fe 3 O 4 MNPs) as a heterogeneous catalyst to remove tetracycline (TC) from aqueous solution. By using XRD, BET, VSM, SEM, TEM and EDX techniques, also, we tried to characterize the catalyst. The effects of pH, H 2 O 2 , catalyst dosages and also initial TC concentration on the degradation process were assessed. Based on the results, it was indicated that at low pH values and initial TC concentrations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(24 citation statements)
references
References 60 publications
2
20
0
2
Order By: Relevance
“…The XRD pattern of Fe 3 O 4 was in a good agreement with the standard Joint Committee for Power Diffraction Studies, (JCPDS No. 19–0629) . The XRD pattern of the synthesized Fe 3 O 4 , which is quite similar to that of pure magnetite, suggests the lack of any impurities in the Fe 3 O 4 structure.…”
Section: Resultsmentioning
confidence: 70%
“…The XRD pattern of Fe 3 O 4 was in a good agreement with the standard Joint Committee for Power Diffraction Studies, (JCPDS No. 19–0629) . The XRD pattern of the synthesized Fe 3 O 4 , which is quite similar to that of pure magnetite, suggests the lack of any impurities in the Fe 3 O 4 structure.…”
Section: Resultsmentioning
confidence: 70%
“…11,[13][14][15][16][17][18][19][20] To keep iron in heterogeneous phase, use of carbon based materials are the advantageous due to its unique catalytic properties including the stability in acidic medium and higher temperature. 21 Jaafarzadeh et al reported the Fenton oxidation of tetracycline, catalyzed by powder activated carbon/Fe 3 O 4 hybrid composite with good stability of the catalyst within 4 h. 22 Nidheesh et al found that iron loaded on activated carbon can effectively degrade rhodamin B in aqueous medium by Fenton process. 23 Degradation of phenol by carbon supported Fe catalyst 24 and orange II removal by Fe supported on carbon nanotubes 25 showed good catalytic activities, but with less stability of the catalyst in terms of the high amount of Fe leaching in the former case aer the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these nanoparticles have enormous specific surface area, large quantity of the reactive surface sites, low toxicity, and excellent magnetic features [18]. Considering mentioned advantages of nano-sized magnetic particles, large adsorption efficiency, significant amount of pollutants adsorption, and quick separation of the adsorbent from the aqueous media through application of an external magnetic field can be expected from applying this method [17, 19, 20]. …”
Section: Introductionmentioning
confidence: 99%